2022
DOI: 10.1128/aem.02356-21
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics of Historical Host Switches in a Bacterial Plant Pathogen

Abstract: Xylella fastidiosa is a globally important bacterial plant pathogen with many hosts; however, the underpinnings of host specificity are not known. This paper contains important findings about the usage of phylogenetics to understand the history of host specificity in this bacterial species, as well as convergent evolution in the pan-genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…In our study, we have found a significant, non-random association between phylogenetic relationships and both the species and taxonomic order of plant hosts (P < 0.0001) based on core phylogenies. These results are consistent with some level of specialization of X. fastidiosa to plant hosts and with the recent analysis of Kahn and Almeida (2022). Moreover, these results were robust to phylogenetic treatment -i.e., the inclusion or exclusion of genomic regions inferred to have histories of recombination.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, we have found a significant, non-random association between phylogenetic relationships and both the species and taxonomic order of plant hosts (P < 0.0001) based on core phylogenies. These results are consistent with some level of specialization of X. fastidiosa to plant hosts and with the recent analysis of Kahn and Almeida (2022). Moreover, these results were robust to phylogenetic treatment -i.e., the inclusion or exclusion of genomic regions inferred to have histories of recombination.…”
Section: Discussionsupporting
confidence: 91%
“…As an example, the cluster corresponding to multiplex displayed the most discordance between the core and accessory trees, with all OTUs contributing to phylogenetic incongruence (Figure 3). Interestingly, our multiplex sample also had more plant host species than our fastidiosa and pauca samples, suggesting the possibility (but by no means proving) that host factors may affect or moderate genome content (27). Nonetheless, we found a significant correlation between distance matrices based on the core and accessory phylogenies (Mantel test, R = 0.1144, P = 0.019), which is consistent with the fact that the two trees had the same three major clades.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In these cases, an in-depth genomic analysis is required to determine whether this gene is conserved in the plasmid or whether it is inserted in the chromosome as with the strains 3124, U24d, J1a12, 9a5c, Hib4 from Brazil. Patterns of inter-and intrasubspecific homologous recombination between Xf subspecies pauca showed that these Brazilian strains have a high number of recombination events [32,33] (M.P. Velasco-Amo, L.F. and B.B.…”
Section: Discussionmentioning
confidence: 99%